Positive inotropic effects of serotonin in atrial EHT: further proof for an atrial phenotype? - Muhammed Sönmez; Margaret Nandudu; Paul Brunnbauer; Carl Schulz; Birgit Klampe; Thomas Schulze; Arne Hansen; Thomas Eschenhagen; Torsten Christ (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Human-induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CM) cultured in the presence of retinoic acid were proposed as a model for human atrium. Since in the human heart positive inotropic effects of serotonin (5-HT) are restricted to the atrium, we investigated whether the presence of 5-HT responses may distinguish between hiPSC-atrial and ventricular CM. Nonfiltered retinoic acid (1 µM) was used to induce an atrial phenotype (hiPSC-aCM) in two different hiPSC lines. Untreated hiPSC-CM were used as controls (ventricular). We measured 5-HT4 receptor ( HTR4 ) expression and 5-HT effects on Ca 2+ currents (I Ca ), force, and action potential in engineered heart tissue (EHT). HTR4 transcript abundance was five times higher in atrial EHT. 5-HT (100 µM) increased I Ca from 5.3 ± 0.8 to 8.1 ± 1.1 pA/pF, prolonged APD 20 from 8.1 ± 1.2 to 12.0 ± 1.2 ms, and shortened APD 90 from 142.3 ± 11.3 to 117.0 ± 6.6 ms in hiPSC-aCM, but not in hiPSC-vCM. 5-HT increased force in atrial EHTs from 0.06 ± 0.01 to 0.10 ± 0.01 mN but not in vEHT. Spontaneous beating rate per minute was increased by 5-HT in aEHT from 151.3 ± 7.5 to 173.7 ± 4.1 and in vEHT from 43.1 ± 4.2 to. 61.3 ± 3.4. Both EHTs contain functional 5-HT receptors, but 5-HT increases I Ca and force only in aEHT, similar to the human heart. In vEHT, 5-HT’s positive chronotropic effect in the absence of I Ca stimulation and inotropic response suggests activation of funny channels. Our findings demonstrate that aEHT shares the typical atrial-selective regulation of I Ca and force by 5-HT, thus making aEHT a promising model to study 5-HT 4 receptors in the human heart.

Grazing by sea urchins is a potential co‐driver of Greenland kelp forest distribution - Jakob Breinholt Kjær; Susse Wegeberg; Mikael K. Sejr; Birgit Olesen; Núria Marbà; Michael Bo Rasmussen; Martin Emil Blicher; Annette Bruhn; Jørgen L. S. Hansen; Jannie Fries Linnebjerg; Dorte Krause‐Jensen (Limnology and Oceanography, 2025)
Grazing by sea urchins is a main driver of kelp forest dynamics causing shifts from kelp forests to urchin barrens in the temperate region but there is limited information on such patterns from the Arctic region. Based on information from 132 underwater video transects along Greenland's West Coast at 59.9–77.8°N, we explored the distribution of kelps and sea urchins, including the occurrence of sea urchin barrens, along latitudinal‐ and depth‐gradients. We observed more extended kelp cover and deeper‐growing kelp forests toward south, although with marked variability among sites. Sea urchins were present along the entire West Coast, with no clear depth‐related pattern, but their densities were generally higher toward north. Kelp cover declined toward deeper, light‐limited waters and was also reduced where sea urchins were abundant, in some cases with urchin barrens within the kelp beds, suggesting a potential top‐down control of kelp distribution by sea urchins. Sea urchins left, on average, 10% of the potential kelp area barren, with the largest proportion (20%) of barren ground toward north. Earlier studies have identified the length of the sea‐ice free period and water temperature as main bottom‐up drivers of spatial distribution of kelp in this region. We conclude that sea urchins are present all along Greenland's West Coast and occur at densities suggesting they may act as local co‐drivers of kelp forest distribution and cover.

Airborne metals and microorganisms during work with historical books – Exposure and biomonitoring - Akila Muthalagu; Mohammad S. Delsuz; Michael Levi; Maria Kippler; Margit W. Frederiksen; Birgit Vinther Hansen; Iben Bak Christensen; Karin Broberg; Anne Mette Madsen (International Journal of Hygiene and Environmental Health, 2025)

Effects and risk assessment of halogenated bisphenol A derivatives on human follicle stimulating hormone receptor: An interdisciplinary study - Valentine Suteau; Lorena Zuzic; Ditlev Høj Hansen; Lisbeth R. Kjølbye; Paul Sibilia; Louis Gourdin; Claire Briet; Mickaël Thomas; Eric Bourdeaud; Hélène Tricoire-Leignel; Birgit Schiøtt; Pascal Carato; et al. (Journal of Hazardous Materials, 2024)

Resilient forests for the future - Annika Perry; Filippos A. Aravanopoulos; Katharina Birgit Budde; Ole Kim Hansen; Christian Rellstab; Hilke Schroeder; Alexandru Lucian Curtu (Tree Genetics & Genomes, 2024)
Forest ecosystems are of global importance, ecologically, economically and culturally. However, despite their fundamental role in mitigating the worst effects of climate change, to date there have been surprisingly few resources devoted to defining, conserving and planning resilient forests for the future. Progress in this field of research, which requires international and interdisciplinary cooperation, collaboration and communication, was presented and discussed at the second biannual conference of the European Research Group, Evoltree ( https://www.evoltree.eu ). Over four days more than 140 scientists met to share developments and to discuss forest ecology, genetics, genomics and evolution with a focus on realising “Resilient Forests for the Future”. From examining evolutionary dynamics and using the past to understand future responses, to evaluating breeding approaches and the sustainable use of forest genetic resources, the conference addressed critical themes with relevance to this topic. The role of genomics in conservation, investigation of biotic interactions and identifying climate resilient forests were also explored. Finally, innovative methods and approaches which promise to increase the scale and speed with which forest evolutionary research can progress were introduced and evaluated. The Evoltree network and conference series provides invaluable opportunities to share knowledge and increase collaboration on forest genetic research, the need for which has never been greater or more urgent.

Combining cross-sectional survey and register data improved the estimate of hepatitis C prevalence among patients attending a psychiatric emergency department in Denmark - Thomas Vemmelund Rose; Peer Brehm Christensen; Peter Hjorth; Lone Wulff Madsen; Janne Fuglsang Hansen; Sandra Dröse; Gustav Bang Harvald; Birgit Thorup Røge; Anne Lindebo Holm Øvrehus (Infectious Diseases, 2024)

Retrieval of patients with hepatitis C who were lost to follow-up in Southern Denmark - Sandra Dröse; Janne Fuglsang Hansen; Birgit Thorup Røge; Anne Lindebo Holm Øvrehus; Peer Brehm Christensen (Infectious Diseases, 2023)

Nearshore Dissolved and Particulate Organic Matter Dynamics in the Southwestern Baltic Sea: Environmental Drivers and Time Series Analysis (2010–2020) - Helena Osterholz; Christian Burmeister; Susanne Busch; Madleen Dierken; Helena C. Frazão; Regina Hansen; Jenny Jeschek; Anke Kremp; Lars Kreuzer; Birgit Sadkowiak; Joanna J. Waniek; Detlef E. Schulz-Bull (Frontiers in Marine Science, 2021)
Dissolved and particulate organic carbon (DOC, POC) and nitrogen (DON, PON) constitute essential nutrient and energy sources to heterotrophic microbes in aquatic systems. Especially in the shallow coastal ocean, the concentrations are highly variable on short timescales, and cycling is heavily affected by different sources and environmental drivers. We analyzed surface water organic carbon and nitrogen concentrations determined weekly from 2010 to 2020 in the nearshore southwestern Baltic Sea (Heiligendamm, Germany) in relation to physical, chemical and biological parameters available since 1988. Mixing of low-DOC North Sea water with high-DOC Baltic Sea water, as well as in situ primary production, were confirmed as the main drivers of organic carbon and nitrogen concentrations. Tight coupling between POC, PON, chlorophyll a and phytoplankton carbon with DON seasonal dynamics corroborated the close relationship between phytoplankton production and degradation of organic nutrients with preferential remineralization of nitrogen. Significant changes in air and water temperature, salinity, and inorganic nutrients over time indicated effects of climate change and improved water quality management in the eutrophic Baltic Sea. Bulk organic nutrient concentrations did not change over time, while the salinity-corrected fraction of the DOC increased by about 0.6 μmol L –1 yr –1 . Concurrently, chlorophyll a and Bacillariophyceae and Cryptophyceae carbon increased, denoting a potential link to primary productivity. The high variability of the shallow system exacerbates the detection of trends, but our results emphasize the value of these extended samplings to understand coupled biogeochemical cycling of organic matter fractions and to detect trends in these important carbon reservoirs.

The impact of age on risk assessment, therapeutic practice and outcome in candidemia - Liv Hesstvedt; Peter Gaustad; Fredrik Müller; Cecilie Torp Andersen; Cathrine Brunborg; Haima Mylvaganam; Rafael Alexander Leiva; Jan Erik Berdal; Trond Egil Ranheim; Bjørn Odd Johnsen; Birgit M. Falch; Gro Grimnes; et al. (Infectious Diseases, 2019)

The Global High Frequency Radar Network - Hugh Roarty; Thomas Cook; Lisa Hazard; Doug George; Jack Harlan; Simone Cosoli; Lucy Wyatt; Enrique Alvarez Fanjul; Eric Terrill; Mark Otero; John Largier; Scott Glenn; et al. (Frontiers in Marine Science, 2019)

Phenotyping carrot (Daucus carota L.) for yield-determining temperature response by calorespirometry - Amaia Nogales; Luz Muñoz-Sanhueza; Lee D. Hansen; Birgit Arnholdt-Schmitt (Planta, 2015)

Diffusion-Weighted MRI for Verification of Electroporation-Based Treatments - Faisal Mahmood; Rasmus H. Hansen; Birgit Agerholm-Larsen; Kurt S. Jensen; Helle K. Iversen; Julie Gehl (The Journal of Membrane Biology, 2011)

Integral assessment of estrogenic potentials in sediment-associated samples - Robert Kase; Peter D. Hansen; Birgit Fischer; Werner Manz; Peter Heininger; Georg Reifferscheid (Environmental Science and Pollution Research, 2009)

Integral assessment of estrogenic potentials of sediment-associated samples - Robert Kase; Peter-D. Hansen; Birgit Fischer; Werner Manz; Peter Heininger; Georg Reifferscheid (Environmental Science and Pollution Research, 2008)

Chemokines, natural killer cells and granulocytes in the early course of Leishmania major infection in mice - Kerstin Müller; Ger Zandbergen; Birgit Hansen; Helmut Laufs; Nicole Jahnke; Werner Solbach; Tamás Laskay (Medical Microbiology and Immunology, 2001)